Why managers hold shares of their firms: An empirical analysis - Ulf von Lilienfeld-Toal; Stefan Ruenzi (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2007)
We examine the relationship between CEO ownership and stock market performance. Firms in which the CEO voluntarily holds a considerable share of outstanding stocks outperform the market by more than 10% p.a. after controlling for traditional risk factors. The effect is most pronounced in firms that are characterized by large managerial discretion of the CEO. The abnormal returns we document are one potential explanation why so many CEOs hold a large fraction of their own company's stocks. We also examine several potential explanations why the existence of an owner CEO is not fully reflected in prices but leads to abnormal returns.
Keywords: G12; G30; 330; CEO-Ownership; Asset Pricing with large shareholders; Börsenkurs; Unternehmensentwicklung; Führungskräfte; Eigentümerstruktur; Wertpapieranalyse; USA